Post-LGM environments and foragers on the move: New data from the lower Altmühl Valley (Franconian Jura, SE Germany). Issue 173 (December 2022) - Barbieri, Alvise; Maier, Andreas; Lauer, Tobias; Mischka, Carsten; Hattermann, Merlin; Uthmeier, Thorsten
Abstract: After the Last Glacial Maximum, the Swabian and Franconian Jura (in SW and SE Germany, respectively) were repopulated by Magdalenian hunter-gatherers within the same communication network. However, while the Magdalenian settlement of the Swabian Jura dates to 17–14 ka cal BP, permanent Magdalenian occupations in the Franconian Jura date to 15–14 ka cal BP. In comparison with its western counterpart, the Franconian Jura was mostly excavated in the early days of archaeological research. Does this different chronology reflect the different history of research? Why did Magdalenian foragers establish permanent occupation in the Franconian Jura nearly 2 millennia after settling in Swabia, despite the fact these regions are only 150 km apart? To address these questions, we reinvestigated two sites in the Altmühl Valley with micromorphology and luminescence dating, namely Felsenhäusl-Kellerhöhle and Klausennische. Our data show that both sites have intact Pleistocene deposits. Among these, we identified sediments dating between 17 and 15 ka that show only rare lithic artifacts and microfeatures indicative of cold and arid conditions. Our work and published data suggest that the steady settlement of Magdalenian foragers in the Altmühl Valley starting 15 ka cal BP coincides with the end of this harsh period and the onset of cool and wetter environments. Data from the Swabian Jura demonstrated that in the Lone Valley, similar environments and Magdalenian occupations commenced earlier, starting 17 ka cal BP. Therefore, we propose that regional environments acted as a barrier against the dispersal of foragers in the Franconian Jura and determined its later Magdalenian occupation. Our research highlighted that different environments, taphonomic processes, and site uses probably coexisted across the German Jura. Therefore, it remains fundamental to expand the multisite data set proposed in this article to further test hypotheses about human/environment interaction in this region. Highlights: After the LGM, different environments coexisted across the German Jura. Cold and arid climate acted as a barrier against the dispersal of foragers. Expansion of cool and wet climate attracted permanent Magdalenian occupation.